GAMBARAN STRES SISWA SMP KELAS 3 SEBELUM MENGIKUTI UJIAN NASIONAL - riskirivaldo riski (Yayasan Pendidikan Medika Indonesia, 2021)
ABSTRACT Stress is a condition of semeone whose not able to adaptation optimally cause of high stressor so occured pshycological problems. Stress is can occure in every age level especially in students whose gonna face the National examination. The aim of this research is to find the description of stress level of grade third students in SMPN 9 Pekanbaru before facing the National examination. This was a Quantitative study with descriptive desaign. The population were all of the third students in SMPN 9 Pekanbaru. Sample were 179 students which taken by Quota sampling technique. The instrument was used questionnare of DASS 42 ( Depression Anxiety Stress Scale ) with 42 questions. The data analyzed was used univariate with distribution frequency for data presentation. The result showed that most of the students which will faced the National examinations were very hard level amount 48 people (26,8%), middle level amount 34 people (19,0%), severe level amount 28 people (15,6%), light level amount 22 people (12,3%). But amount 47 people (26,3%) were don’t felt stress ( normal ). Based on the result of this study it is suggested to the school to provide activities that can make students take the national exam. References : 37 (2002-2016)Keywords : National Examination, Stress, Student